Spatio-temporal analysis of environmental noise in institutional area - Abdullah S.; Akhtari M.I.; Ismail M.; Ahmed A.N.; Mansor W.N.W.; Zulkifli M.F.R. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
Environmental noise is identified as unwanted sound arises mainly from motor vehicles. The increasing number of motor vehicles in institutional area would negatively affect the environment and students learning process. This study assesses the variability of environmental noise in institutional area in terms of temporal and spatial analysis. Noise level was taken in Universiti Malaysia Terengganu (UMT) campus by using sound level meter at varying time intervals of 0700hrs-1000hrs (morning), 1100hrs 1400hrs (afternoon) and 1500hrs 1800hrs (evening) and noise mapping was constructed by using Surfer14 and SketchUp software. Lmax (78.8 dBA, weekday (WD) and 84.4 dBA, weekend (WK)), LAeq (75.0 dBA, WD and 75.5 dBA, WK), Lmin (43.9 dBA, WD and 41.3 dBA, WK), L10 (66.8 dBA, WD and 58.5 dBA, WK) and L90 (47.5 dBA, WD and 44.4 dBA, WK) were evaluated. Motor vehicles from Class M (cars and buses) shows strong correlation with noise level (Spearmans correlation coefficient, r=0.74, p<0.01, WD) while Class L (motorcycle) shows strong correlation (Spearmans correlation coefficient r=0.59, p<0.01, WK). The finding from this study is important for UMT management team to control noise pollution in campus in line to reduce noise exposure towards university students and staff. BEIESP.